Method of lock-up construction / Ahmad Zaidi Mohamed Anuar - Mohamed Anuar, Ahmad Zaidi (Universiti Teknologi MARA, Perak, 2013)
This report directly describes the processes and methods of construction in the police lock-up. It is produced based on the experience of five months stationed at the construction site. This report is divided into several parts, which started with the company background and the background of the construction project. As a result of study and observation found that the method of construction of the lock-up is not easy and it looks very different as compared to other construction methods. Then described more in detail about the methods involved and used in the construction of the lock-up which includes the construction of reinforcement bar on the floor, walls and roof floor and once blended concrete mix. During the construction stage, there are some problems and changes in the opening lock-up and the report ended with some suggestions and can solve the problem identified. In conclusion, this report will explain in more detail the process and practical lock-up construction method for the reader.